2021
DOI: 10.3389/fphys.2021.671599
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Genes of Megalurothrips usitatus (Bagrall) Against Beauveria brongniartii and Akanthomyces attenuatus Identified Using RNA Sequencing

Abstract: Megalurothrips usitatus (Bagrall) is an important pest of legumes worldwide, causing great economic loss every year. Beauveria brongniartii and Akanthomyces attenuatus have shown considerable pathogenicity against M. usitatus in our previous studies. The medial lethal concentration (LC50) and the sublethal lethal concentration (LC25) of B. brongniartii isolate SB010 against M. usitatus were 8.38 × 105 and 1.73 × 105 conidia mL−1, respectively, whereas those of A. attenuatus isolate SCAUDCL-53 against M. usitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Their findings revealed that 654 and 1,681 genes were differentially expressed at 48 and 72 h post-infection, respectively, compared to the control. Chen et al [26] also observed a lower number of DEGs in Megalurothrips usitatus post-A. attenuatus infection when compared to infection with Beauveria brongniartii.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Their findings revealed that 654 and 1,681 genes were differentially expressed at 48 and 72 h post-infection, respectively, compared to the control. Chen et al [26] also observed a lower number of DEGs in Megalurothrips usitatus post-A. attenuatus infection when compared to infection with Beauveria brongniartii.…”
Section: Discussionmentioning
confidence: 92%
“…The qRT-PCR was conducted on a Bio-RAD iQ5 thermocycler with the following temperature settings: initial denaturation at 94 °C for 30 minutes, followed by 39 cycles of 94 °C for 5 seconds, 55 °C for 30 minutes, and 72 °C for 10 seconds, followed by a melt curve of 65-95 °C, incrementing 0.5 °C for 0.05 seconds. As described earlier, the 2 -ΔΔCt technique was used to calculate relative expression levels using β-actin as an internal control [21,25,26,69,70].…”
Section: Qrt-pcr Verification Of Dgesmentioning
confidence: 99%
“…Megalurothrips usitatus (Bagnall) is a major pest of leguminous crops (Fabales: Fabaceae), such as cowpea (Vigna unguiculata [Linnaeus] Walp. ), in southern China. M. usitatus primarily relies on rasping–sucking mouthparts to penetrate plant tissues, actively absorb its contents during feeding, and reduce the photosynthetic capacity of host plants for deformities and scars of petals and fruits .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical pesticides, such as spinetoram, acetamiprid, chlorfenapyr, and fluridine nitrile, are frequently applied to control this pest; however, this rapidly causes severe resistance and environmental pollution [ 3 ]. Moreover, chemical control is usually difficult because this pest is able to hide inside the flowers and pods of plants [ 4 ]. Therefore, developing alternative approaches to control this pest is an urgent matter.…”
Section: Introductionmentioning
confidence: 99%